26.1k views
1 vote
What is -6(9-9v)
Please only answer with the answer

2 Answers

6 votes
Rearrange terms
-6(9-9v)
-6(-9v+9)

Distribute
-6(-9v + 9)
54v - 54

Then, -6(9-9v) equals to 54v - 54
User Hady
by
5.5k points
1 vote

Answer:

v = 1

Explanation:

-6(9-9v)

-6*9 = -54

-6*(-9v) = 54v

-54+54v = 0

+54 +54

54v = 54

divide both sides by 54

v = 1

User David ROSEY
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.